Ubiquinol ameliorates endothelial dysfunction and increases expression of miRNA-34a in a rat model of pulmonary hypertension - Tatyana A. Kuropatkina; Nadezda V. Pankova; Natalia A. Medvedeva; Oleg S. Medvedev (Belgorod National Research University, 2021)
Introduction: In this research, we evaluate the effect of intravenously administrated solubilized ubiquinol on 4-week monocrotalin-induced pulmonary hypertension (PH) in rats. Materials and methods: To reproduce the model, some male Wistar rats were subcutaneously injected with alcohol solution of monocrotaline 60 mg/kg and the rest - with alcohol solution (Control). Those with monocrotaline (MCT) were divided into 3 groups. They underwent intravenous administration of 1% ubiquinol solution 30 mg/kg (MCT-Ubiquinol), the vehicle (MCT-Vehicle) and saline (MCT-saline) three times on days 7, 14 and 21, depending on the group. The hemodynamic parameters were measured in anesthetized rats on day 29. Right ventricle hypertrophy, pulmonary arteries reactivity and expression of miRNA-21 and miRNA-34a were estimated after euthanasia. Results and discussion: All MCT-groups demonstrated an increase in right ventricle systolic pressure and hypertrophy in comparison with the control group. An increase in lung weight was shown in MCT-Vehicle and MCT-Saline; however, the MCT-Ubiquinol indicators did not differ from those of the Control. There was an increased vasodilatation response to acetylcholine at concentrations of 1*10-6M and 1*10-5M in MCT-Ubiquinol in contrast to the other two MCT-groups. A significantly lower level of expression of miRNA-34a was observed in MCT-Ubiquinol. Conclusion: Our findings suggest that a triple ubiquinol injection influences pulmonary changes and endothelium-depended vasodilatation, which contributes to pulmonary vascular tone and reactivity. A decrease in miRNA-34a expression in MCT-Ubiquinol group demonstrates the ubiquinol anti-inflammatory properties.